Bioelectrical activity of interneyron pools of spinal cord an early stage of experimental compressive neuropathy and prednisolone effects - А. G. Rodynskiy; І. A. Gutnik; A. N. Gninenko; К. V. Pisarevskaya (Zaporožskij Medicinskij Žurnal)
In experiments on white rats examined the activityof interneyron pools of spinal cord (SC) in the early stages (from the 10th day) of compression neuropathy (CN) of the sciatic nerve.